Variação da biomassa em guildas tróficas de peixes em resposta a seca em um reservatório no semiárido - Martins, Luiz Paulo da Costa (Universidade Federal Rural do Semi-Árido, 2016)
Studies on the composition of trophic guilds of fish is crucial to determine the trophic structure and resource use by different species in environments due to temporal variations, for example, a prolonged drought, taking effect on the richness and abundance of these species modifying biodiversity. So this paper aims to show that the reduction in the volume of water and rainfall reservoir of Santa Cruz promotes negative changes in the biomass of fish species in the trophic guilds. Data were used precipitation (mm), a percentage of the accumulated water volume and biomass of fish every three months between February 2010 and November 2014. For the analysis of CPUE data were used, in order to verify significant changes for each trophic guild it was applied PERMANOVA was later applied the nonparametric Kruskal-Wallis test to determine which species has greater contribution of CPUE between years of collecting. To check changes in the formation of guilds was made a presence and absence analysis for all species and finally in order to verify the temporal organization of trophic guilds was applied nonparametric correlation Spearman test. They found 22 species with temporal variation distributed in five trophic guilds. The guild Detritivorous/Iliófaga showed higher biomass followed by guilds Carcinophaga, Insectivorous, Omnivorous and Piscivorous. Our results show that the temporal reduction in the biomass of trophic guilds Detritivorous/Iliófaga and Carcinophaga are related to the water and precipitation volume reduction factors, as other guilds their temporal biomass oscillations can this related to several factors such as resource exploitation food in greater abundance in a given year, favoring the presence of some guilds
Keywords: Guildas tróficas; Variações temporais; Biomassa; Reservatório de Santa Cruz; Trophic guilds; Temporal variations; Biomass; Reservoir of Santa Cruz; CIENCIAS AGRARIAS::MEDICINA VETERINARIA